2006
DOI: 10.1016/j.jneuroim.2006.03.006
|View full text |Cite
|
Sign up to set email alerts
|

T-cell apoptosis in human glioblastoma multiforme: Implications for immunotherapy

Abstract: We used immunohistochemistry and flow cytometry to assess apoptosis in human glioblastoma multiforme (GBM). Our immunohistochemical study revealed apoptosis of glioma cells expressing glial fibrillary acidic protein and of CD3 + T cells infiltrating GBM. To quantify and phenotype the apoptotic T cells, we performed flow cytometry on lymphocytes separated from GBM. The cells were stained with annexin-V-FLUOS/propidium iodide to identify apoptosis. We found that high proportions of both the CD4 + and CD8 + T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Like many other type of cancer, the glioma microenvironment become immune suppressive where primed CD8+ cytotoxic T-cells become inhibited or induced to become apoptotic and thus cannot execute their function [57,58]. In addition, there is increased recruitment of other immune suppressive cells like FOXP3+ regulatory T-cells [59].…”
Section: Cscs In Gliomamentioning
confidence: 99%
“…Like many other type of cancer, the glioma microenvironment become immune suppressive where primed CD8+ cytotoxic T-cells become inhibited or induced to become apoptotic and thus cannot execute their function [57,58]. In addition, there is increased recruitment of other immune suppressive cells like FOXP3+ regulatory T-cells [59].…”
Section: Cscs In Gliomamentioning
confidence: 99%
“…6 Our recent work has shown that these cells undergo apoptosis at a high rate. 7 Dendritic cells (DCs) represent a subgroup of white blood cells that are central to the coordination of adaptive immunity owing to their role as professional antigen-presenting cells. They are capable of presenting antigens together with major histocompatibility complex (MHC) I and II molecules 8,9 and as such can stimulate Th4 helper cells as well as cytotoxic T cells.…”
Section: Introductionmentioning
confidence: 99%
“…9), supporting the idea that some types of tumors may suppress local immune function by using ECMs to impair lymphocyte infiltration. Our findings provide a plausible explanation at the molecular level to explain why CD3 + T lymphocytes were less frequently observed in glioma tumor nodules but scattered throughout the parenchyma (45,46). Understanding the mechanisms of lymphocyte migration and how they are modulated by a tumor matrix will illuminate new targets for boosting immune surveillance against tumors.…”
Section: Discussionmentioning
confidence: 73%